Nagari Kamang Mudiak pada Masa Pergolakan PRRI (1958-1961) - Budiman, M; Hardi, Etmi (Lembaga Yasin AlSys, 2023)
This research examines socio-cultural, economic and political life and the role and involvement of the Nagari Kamang Mudiak community during the PRRI Upheaval. The purpose of this study is to describe how socio-cultural, economic and political life is, as well as explain the role and involvement of the Nagari Kamang Mudiak community during the 1958-1961 PRRI upheaval. The research method used is the historical research method which goes through four stages which include; heuristic (data collection), source criticism (source testing), interpretation (interpreting and analyzing sources), and historiography (history writing). This research is included in the qualitative descriptive research by utilizing data from various primary and secondary sources. Apart from documents such as personal notes, transcripts of interview recordings, the primary data of this study was strengthened by interviews with several members of the community and figures involved for oral data. As for the secondary sources obtained from books, articles, magazines which are certainly relevant to this research. The PRRI upheaval involving Nagari Kamang Mudiak made the socio-cultural and economic conditions of the community worse off than before. In fact, there was a lot of violence that made people feel anxious and afraid. The violence was not only from the Central Army but also from the people of Nagari Kamang Mudiak themselves. With the topographical area of Nagari Kamang Mudiak which is surrounded by forests and hills and the many people who oppose the central government, this area has an important role during times of upheaval. From this research it can be concluded that the life of the people of Nagari Kamang Mudiak is declining and this area has an important role in the PRRI upheaval, both from its geographical condition to the involvement and participation of the community.